2002
DOI: 10.2320/matertrans.43.246
|View full text |Cite
|
Sign up to set email alerts
|

Ageing Processes in Al-Mg-Si Alloys during Continuous Heating

Abstract: The precipitation behaviours during continuous heating in the Al-Mg 2 Si alloys with excess Mg and Si contents have been investigated by means of Vickers hardness measurements, differential scanning calorimetry and transmission electron microscopy. The first exothermic reaction occurring at the lowest temperatures is due to the annihilation of quenched-in vacancies by the collapse of vacancy clusters and the migration of vacancies to various sinks such as grain boundaries. The prismatic dislocation loops forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 30 publications
4
29
0
Order By: Relevance
“…In the previous continuous heating experiment, 18) the intermediate phases observed were limited, and the formation of Type-A and C rods could not be recognised. The phases precipitated during isothermal ageing processes are summarised in Table 2.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the previous continuous heating experiment, 18) the intermediate phases observed were limited, and the formation of Type-A and C rods could not be recognised. The phases precipitated during isothermal ageing processes are summarised in Table 2.…”
Section: Discussionmentioning
confidence: 73%
“…Since the precipitation of cuboid β-Mg 2 Si particles has been discussed in detail in the previous studies, 8,18) the formation of other intermediate phases is examined here. In the excess Si alloys, Type A rods starts to precipitate after β needle and fine Si particle formation at 210…”
Section: Discussionmentioning
confidence: 99%
“…Dutta and Allen 24) reported 33.1 kJ/mol for 6061 alloy, however Doan et al 25) determined 79 kJ/mol for the same process of the same alloy. In addition, Ohmori et al 26) calculated activation energy of 52.364.5 kJ/mol for this process of AlMgSi alloy. Therefore, our value for the activation energy of the clustering process is within the most acceptable values found in the literature.…”
Section: Dsc Curvesmentioning
confidence: 99%
“…The second group of clusters, speculated to be descendants of the first Si-rich clusters, is shown to exhibit Mg-enrichment while growing 9,24,25,30 . It has been reported that a larger Si content in the alloy composition promotes cluster nucleation and leads to a finer distribution of β precipitates at later stages of aging 9,31,32 . The morphology of early-stage precipitates is generally reported from atom probe investigations to be spherical 9,24,28,29 .…”
Section: Introductionmentioning
confidence: 99%